EUROPEAN UNION AND THE UNITED STATES OF AMERICA: AN ECONOMETRIC INVESTIGATION ON THE PARADIGM SHIFT IN THE GDP’S GROWTH RATE TREND - Karuvalappil, Dibin Kodanghat; Balakrishnan, Archana (Indian Journal of Finance and Banking, 2022)
The recent war between Ukraine and Russia is yet another instance that emphasizes that economic overdependence may destroy the economic fabric of a nation. Taking this premise into consideration, this study aims to examine the long-term and short-term connection between the European Union and the United States GDP growth rates using tools like linear regression, Granger causality test, and impulse response function. Quarterly GDP figures of the European Union and the United States were taken for the period spanning 22 years, starting from quarter 2 of the financial year 1998-1999 to quarter 4 of the financial year 2018-2019. The Regression model and the Granger Causality test prove that the United States’ GDP growth rate is influenced by that of the European Union in the short-run as well as in the long-run, but the EU’s GDP is independent and does not follow the former. The possible explanation can be the trade surplus of the European Union over the United States in the recent past. Hence, the authors are of the opinion that a much more balanced trade between these two powerful economies would ensure the stabilization of the global trade and stability of the global power equation.JEL Classification Codes: F40, F43, F44.